Reflexiones sobre el uso de diarios de los estudiantes en una investigación docente - Alves, Flávio Soares [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
This article reflects on the use of students’ diaries as research material. It starts by describing the way this type of writing was established in an undergraduate Physical Education course, which proposes to experience concepts and undergo experiences with body practices in the context of academic education and self-knowledge. We underscore singularities and references that supported the making of that material and the ethical-methodological decisions taken to consider them in a study focused on finding out the effects of the discipline in question on the invention of students’ subjectivities. We observe that invention appears in the diaries, but the plurality of expressions it supports demand dialogic reflections, otherwise its conflicting dimension would escape the research. However, how is it possible to reconcile conflicting thoughts? This article seeks answers to this question based on the research produced and on the Philosophy of Difference.
Reflexões sobre o uso de diários dos alunos em uma pesquisa docente
Reflections about the use of students’ diaries in a research conducted by teachers
Keywords: Body practices; Philosophy; Self-knowledgem Diaries